Anti-Omp34 antibodies protect against Acinetobacter baumannii in a murine sepsis model. (December 2021) - Naghipour Erami, Aleme; Rasooli, Iraj; Jahangiri, Abolfazl; Darvish Alipour Astaneh, Shakiba
Abstract: Acinetobacter baumannii, an opportunistic extracellular pathogen is one of the major causes of nosocomial infections. Omp34, also known as Omp33-36, is a bacterial porin protein involved in the virulence and fitness of this pathogen by adhesion to the host cell. This antigen nominated as an appropriate candidate for immunization against A. baumannii . In this study, the expression of the recombinant Omp34 (rOmp34) was carried out in E. coli BL21 (DE3). The immunogenicity of the rOmp34 in A. baumannii was studied in a murine sepsis model. Antibody response in mice injected with the recombinant protein was assessed using indirect ELISA. Bactericidal activity of rOmp34-immunized mice sera (1:10 dilution) against A. baumannii ATCC 19606 after 0, 1, 2, 4, and 8 h of incubation at 37 °C was assessed. In addition to survival rate, load of bacteria in liver and spleen of the infected mice were evaluated. A high titer of specific antibody equivalent to optical density of 1.54 ± 0.06 against rOmp34 was elicited in the immunized mice sera. Viability of the A. baumannii incubated 8 h with immunized mice sera was 64%. Homogenized liver and spleen samples of the control mice challenged with A. baumannii were loaded with 8 × 10 3 and 9 × 10 3  CFU per gram tissue respectively 48 h post-challenge as against complete clearance of A. baumannii in the immunized group. The protective immunity was achieved by challenging the mice groups with 5 × LD50 of live A. baumannii . Omp34 can be nominated as an immunogen that can bring about protection against Acinetobacter baumannii . Highlights: Omp34 is a porin protein involved in the virulence and fitness of A. baumannii . Recombinant Omp34 (rOmp34) was expressed and studied as immunogen in a murine model. rOmp34-immunized mice sera exhibited bactericidal effect against A. baumannii . A. baumannii was completely cleared from liver and spleen in the immunized group. rOmp34 is nominated as a potent candidate for immunization against A. baumannii .